Senjangan Anggaran Dipengaruhi Oleh Partisipasi Anggaran dan Komitmen Organisasi Di SKPD Provinsi Sumatera Barat - Gerry Hamdani Putra; Zeky Sepriadi (JURNAL PUNDI, 2022)
The Impact of Budget Participation and Organizational Commitment on Slack Budgeting (SKPD Province West Sumatera Case Study.) In fact, all local government agencies, as well as the central government, must have adequate and effective budgets. The SKPD (Regional Work Unit) in West Sumatra is a regional government agency that manages all existing budgets. The aim of this study was first to find out how budget participation affects budget congestion. Second, understand the impact of organizational participation on budget congestion in the SKPD in West Sumatera. The population in this study is a sub-program and finance of the SKPD in West Sumatra. The sampling technique in this study used targeted sampling. The sample for this study included 18 program department managers and all departmental and finance staff involved in budgeting. The results of this study show that: 1) Family participation has a significant positive impact on family idleness. The value of the budget participation coefficient is 2,907 > t Table 1,998, with a significance level of 0.005 (<0.05). 2) Organizational engagement negatively and significantly affects budget underutilization. The value of the organizational commitment coefficient was -4.376 < t Table 1.998 with a significance level of 0.000 (< 0.05).